Knowing in Uncertainty. On Epistemic Conditions Differentiated for Situations in Varying Degrees of Uncertainty, the Distinction Between Hierarchical and Flat Ontology, and the Necessary Merger With the Axiological Domain of Values. - Roo, Gert de (Taylor & Francis, 2021)
This paper adds axiology to ontology and epistemology. These three together address the ultimate questions of what (is being observed), how (to know and respond) and who (adds meaning). This is not about producing knowledge about one true reality. Instead, these three aspects will differentiate their questions about the what, how and who, depending on the circumstances. As these circumstances differ in varying degrees of uncertainty, it is the uncertainty of a situation that determines which ontological, epistemological and axiological questions are asked. This paper proposes three categories into which these questions can fall, for simple, complex and highly complex issues. For each of these categories of ‘uncertainty’, the ontological, epistemological and axiological questions must be in balance. With the addition of axiology and the differentiation of reality into various uncertainties, a much more powerful method of knowing and understanding the world in which we live arises.
Keywords: Planungsphilosophie; Planungstheorie; Unsicherheit; Wissensbasis; Realität; Wahrnehmung; Bedeutung; Wertung; Planungsverständnis; Differenzierung